Human factors in contingency operations. Issue 2 (10th June 2016) - Mercer, Simon J; Khan, MA; Scott, T; Matthews, JJ; Henning, DCW; Stapley, S
Abstract : The UK Defence Medical Services are currently supporting contingency operations following a period of intensive activity in relatively mature trauma systems in Iraq and Afghanistan. Among the key lessons identified, human factors or non-technical skills played an important role in the improvement of patient care. This article describes the importance of human factors on Role 2 Afloat, one of the Royal Navy's maritime contingency capabilities, and illustrates how they are vital to ensuring that correct decisions are made for patient care in a timely manner. Teamwork and communication are particularly important to ensure that limited resources such as blood products and other consumables are best used and that patients are evacuated promptly, allowing the facility to accept further casualties and therefore maintain operational capability. These ideas may be transferred to any small specialist team given a particular role to perform.